Optimizing apothecary through medicinal plant cultivation and education of elderly posyandu cadres in Tegalwaras - Nur Ismiyati; Hendra Rohman; Purwanto Purwanto; Ronggo Nurcahyo; Iramie Duma Kencana Irianto (Universitas Muhammadiyah Magelang, 2023)
As people age, the prevalence of degenerative diseases increases. These diseases can reduce the quality of life and often cause fatal effects, and this happens a lot in Tegalwaras hamlet. Treatment with modern medicine sometimes causes problems such as relatively expensive prices and dangerous side effects so alternatives such as herbal medicines are needed. This community service aims to increase the knowledge of Posyandu Lansia cadres in Tegalwaras about herbs as a therapy for degenerative diseases through counseling and planting medicinal plants. The method of implementation is the preparation stage, counseling, planting medicinal plants, monitoring and evaluation. The results of the program showed an increase in knowledge of 50% after the counseling was carried out.